Аналіз існуючих застосунків для розпізнавання кулінарних страв - Подшивалова, О. Є. (ХНУРЕ, 2024)
The functionality of applications related to the recognition of products and culinary dishes, as well as their classification by allergens and belonging to a group of certain products that can be limited or excluded from the diet while following diet therapy, is considered and analyzed. There are no Ukrainian analogues of culinary classification applications, no applications with similar functions or information on their development. Given this, it can be argued that this area is quite promising
Keywords: розпізнавання кулінарних страв; culinary dishes